2017
DOI: 10.15585/mmwr.mm6635e1
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs: Recent Trends in Stroke Death Rates — United States, 2000–2015

Abstract: IntroductionThe prominent decline in U.S. stroke death rates observed for more than 4 decades has slowed in recent years. CDC examined trends and patterns in recent stroke death rates among U.S. adults aged ≥35 years by age, sex, race/ethnicity, state, and census region.MethodsTrends in the rates of stroke as the underlying cause of death during 2000–2015 were analyzed using data from the National Vital Statistics System. Joinpoint software was used to identify trends in stroke death rates, and the excess numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(178 citation statements)
references
References 23 publications
3
170
0
5
Order By: Relevance
“…From the information available in this database, we included demographic data (age, race/ethnicity, sex, and education status). Race/ethnicity was categorized into five mutually exclusive groups: non‐Hispanic whites, non‐Hispanic blacks, non‐Hispanic Asian/Pacific Islanders, and Hispanics (who could be of any race) . Data for the American Indian and Alaskan native were unreliable due to small number of outcomes and were therefore excluded from final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…From the information available in this database, we included demographic data (age, race/ethnicity, sex, and education status). Race/ethnicity was categorized into five mutually exclusive groups: non‐Hispanic whites, non‐Hispanic blacks, non‐Hispanic Asian/Pacific Islanders, and Hispanics (who could be of any race) . Data for the American Indian and Alaskan native were unreliable due to small number of outcomes and were therefore excluded from final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, effective imaging methods can help identify relevant pathophysiological changes and provide valuable information for the clinician. In their studies, von Morze et al and Cho et al 3,4 used 7T MR imaging systems to reveal the lenticulostriate artery by MRA and found that non-invasive evaluation of the lenticulostriate artery can be achieved, but the 7T MR system has not yet been applied in clinical practice. However, the images of lenticulostriate arteries based on the 3T MR imaging system and the 3D-HRVWI sequence obtained in this study were satisfactory, suggesting a potential for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The latter have a flexible heel that stores potential energy during early stance phase that is then released through recoil of the material in the late stance and early swing phase. Partial foot prosthesis options include toe fillers with or without orthosis and shoe modifications [27].…”
Section: Lower Limb Prosthesismentioning
confidence: 99%